Formation of porous structures in production technology of construction materials based on building gypsum plaster - Anna I. Kurmangalieva; Lyubov A. Anikanova; Aleksander I. Kudyakov; Aleksey B. Steshenko; Aleksander F. Buryanov; Nadezhda A. Lukyanova; Aleksander S. Inozemtsev; Segey S. Inozemtsev (Нанотехнологии в строительстве, 2023)
ABSTRACT: Introduction. This article presents the results of the research works on formation of building gypsum plaster porous structure with the use of recovered anhydrite raw materials and chemical additives, and describes a method for production of wall materials. The relevance of this paper is stipulated by the need to expand the range and increase the manufacture of heat-insulating and structural-heat-insulating products based on gypsum binders and local mineral raw materials, as well as the development of technologies to ensure the production of gypsum materials with improved performance. The authors proposed certain methods for forming the porous structure of building gypsum plaster and improving its performance in terms of porosity and thermal conductivity through the use of modified recovered raw materials and chemical additives of calcium chloride and sodium carbonate. Materials and methods. The study of the effect of modifying additives on the properties of the mixture was carried out using gypsum paste of normal consistency (NC = 55%). The preparation of samples and testing were performed according to the methods specified in the national standards with the use of porous additives of calcium carbonate, fluoroanhydrite and chemical additives for the rheological properties of the mixture, average density and strength of the samples, the patterns and mechanism of the processes of gypsum stone structure formation were established. Results. The application of fluoroanhydrite modified in the disintegrator with an equimolar amount of calcium carbonate leads to a decrease in the average density of the samples to 40% with evenly distributed pores. The analysis of the microstructure of heat-insulating material samples with a density of 550 kg/m3 showed that the average diameter of micropores is 0.45 mm, while the thermal conductivity of samples with complex chemical additives has the thermal conductivity coefficient of 0.25 W/m°C, which is 30% lower than the thermal conductivity of samples without complex additives. Conclusions. The results obtained create the basis for using recovery raw materials and domestic modifying additives as a pore-forming agent, which allow regulating the structure of gypsum stone in order to produce effective wall materials